PRMT7 methylates eukaryotic translation initiation factor 2α and regulates its role in stress granule formation - Haghandish, Nasim (Mol Biol Cell, 2019)
Protein arginine methyltransferases (PRMTs) are a family of enzymes that modify proteins by methylating the guanidino nitrogen atoms of arginine residues to regulate cellular processes such as chromatin remodeling, pre-mRNA splicing, and signal transduction. PRMT7 is the single type III PRMT solely capable of arginine monomethylation. To date, other than histone proteins, there are very few identified substrates of PRMT7. We therefore performed quantitative mass spectrometry experiments to identify PRMT7’s interactome and potential substrates to better characterize the enzyme’s biological function(s) in cells. These experiments revealed that PRMT7 interacts with and can methylate eukaryotic translation initiation factor 2 alpha (eIF2α), in vitro and in breast cancer cells. Furthermore, we uncovered a potential regulatory interplay between eIF2α arginine methylation by PRMT7 and stress-induced phosphorylation status of eIF2α at serine 51. Finally, we demonstrated that PRMT7 is required for eIF2α-dependent stress granule formation in the face of various cellular stresses. Altogether, our findings implicate PRMT7 as a novel mediator of eIF2α-dependent cellular stress response pathways.